IMPLEMENTATION OF SIMPLE FOGGING INNOVATION AS A PREVENTIVE EFFORT FOR DENGUE HEMORRHAGIC FEVER - Daviq Ayatulloh; Diah Priyantini; Khalifatus Zuhriyah Alfianti; Nurul Fahmi Rizka Laily; Ahmad Hasan Basri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The rapid spread of dengue fever can cause epidemics and result in deaths within a short period of time. One effort to eradicate this mosquito is fogging. The high incidence of Dengue Hemorrhagic Fever (DHF) in Dungus Village is caused by poor environmental conditions, such as clogged drainage channels, inadequate waste-disposal facilities, and large amounts of garbage thrown onto the streets, which mark the beginning of the high reproduction rate of the Aedes aegypti mosquito. The purpose of this community service activity was to increase community awareness and behavior through the implementation of simple fogging innovation as a preventive measure against dengue fever outbreaks. The method used was Participatory Action Research (PAR), conducted in three stages: planning, implementation, and evaluation. The planning stage consisted of observation and interviews. The implementation stage consisted of counseling and implementation of the simple fogging innovation, and the evaluation stage was carried out to measure the success of the community empowerment program in overcoming DHF. The results of the community service activity after evaluation showed that knowledge was in the good category (74.3%), attitudes were in the good category (77.1%), and actions mostly showed a good category (68%). After the community service activity was implemented, community behavior in preventing DHF using simple fogging innovation showed good behavior.